1999
DOI: 10.1515/cclm.1999.155
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Platelet Counting in an Insidious Case of Pseudothrombocytopenia

Abstract: Anticoagulant-induced aggregation of platelets leads to pseudothrombocytopenia. Blood cell counters generally trigger alarms to alert the user. We describe an insidious case of pseudothrombocytopenia, where the complete absence of Coulter counter alarms both in ethylenediaminetetraacetic acid blood and in citrate or acid citrate dextrose blood samples was compounded by the fact that the massive aggregates were exclusively found at the edges of the blood smear. Non-recognition of pseudothrombocytopenia can have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 11 publications
1
20
1
1
Order By: Relevance
“…Segundo Pinteric et al (1975), o EDTA promove alterações na membrana dos eritrócitos de humanos, modificando sua morfologia e desencadeando o processo de hemólise osmótica. Vários autores relataram agregação de eritrócitos, plaquetas e, principalmente, leucócitos, associada à presença de EDTA (Deol et al, 1995;Lombarts et al, 1999). O volume globular de sangue de aves e répteis colhidos com EDTA e Heparina foi similar.…”
Section: Introductionunclassified
“…Segundo Pinteric et al (1975), o EDTA promove alterações na membrana dos eritrócitos de humanos, modificando sua morfologia e desencadeando o processo de hemólise osmótica. Vários autores relataram agregação de eritrócitos, plaquetas e, principalmente, leucócitos, associada à presença de EDTA (Deol et al, 1995;Lombarts et al, 1999). O volume globular de sangue de aves e répteis colhidos com EDTA e Heparina foi similar.…”
Section: Introductionunclassified
“…These antiplatelet antibodies, usually IgG or IgM, and rarely IgA, recognize platelet antigens on the platelet membrane modified by EDTA [10][11][12][13]. In contrast to serious and potential life-threatening causes of thrombocytopenia [14][15][16]. EDTA-PTCP is solely an in vitro effect without any clinical relevance [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the prior addition of aminoglycosides to anticoagulants completely prevented the aggregation of platelets in EDTA-dependent PTCP subjects although the mode of action is not known [10]. In addition, the supplementation of aminoglycosides to EDTA-anticoagulated samples after blood withdrawal induced dissociation of aggregated platelets in blood samples from patients with EDTA-dependent PTCP [10,14,15]. Confirmation of EDTA induced thrombocytopenia is best helped by a method that is easy and perpetually effective as is said of the addition of aminoglycosides either before or after collecting the specimen.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA-PTCP occurs due to anti-platelet autoantibodies that cause platelet clumping in the presence of EDTA (4,8). These antibodies, usually IgG but also IgM and IgA, recognize platelet antigens on the platelet membrane modified by EDTA (1,9), which results in platelet agglutination.…”
Section: Discussionmentioning
confidence: 99%